Molecular Bases for the Regulation of Adventitious Root Generation in Plants - Li, Shi-Weng (Frontiers in Plant Science, 2021)
The formation of adventitious roots (ARs) is an ecologically and economically important developmental process in plants. The evolution of AR systems is an important way for plants to cope with various environmental stresses. This review focuses on identified genes that have known to regulate the induction and initiation of ARs and offers an analysis of this process at the molecular level. The critical genes involved in adventitious rooting are the auxin signaling-responsive genes, including the AUXIN RESPONSE FACTOR (ARF) and the LATERAL ORGAN BOUNDARIES-DOMAIN (LOB) gene families, and genes associated with auxin transport and homeostasis, the quiescent center (QC) maintenance, and the root apical meristem (RAM) initiation. Several genes involved in cell wall modulation are also known to be involved in the regulation of adventitious rooting. Furthermore, the molecular processes that play roles in the ethylene, cytokinin, and jasmonic acid signaling pathways and their crosstalk modulate the generation of ARs. The crosstalk and interaction among many molecular processes generates complex networks that regulate AR generation.